The Effectiveness of Acupressure Versus Birth Ball on Reducing Labor Pain and Shortening the First Stage of Labor: A Comparative Study - Herlina Simanjuntak; Hajar Nur Fathur Rohmah; Ika Kania Fatdo Wardani (Media Publikasi Cendekia Indonesia, 2026)
Childbirth is a physiological process involving significant physical, emotional, and hormonal changes. Severe, uncontrolled labor pain can lead to an unpleasant experience and complications, including prolonged labor fetal distress and postpartum hemorrhage. A holistic approach incorporating non-pharmacological methods, such as birth ball exercises and acupressure at LI4 (Large Intestine 4) and SP6 (Spleen 6) points, may alleviate pain by modulating endorphin and cortisol levels, thereby optimizing labor. This quasi-experimental study with a pretest-posttest control group design aimed to compare the effectiveness of acupressure and birth ball exercises on pain intensity and the duration of the first stage of labor. Conducted at the independent midwifery practice Iin Sepnita between March and August 2025, it recruited 48 participants via purposive sampling (24 per group) based on inclusion criteria. Data were collected using a Visual Analogue Scale (VAS), an active phase observation sheet, and a partograph. Analysis employed descriptive statistics and the Mann-Whitney U test. Results demonstrated that birth ball exercise was more effective than acupressure in reducing pain intensity and shortening the first stage of labor. This finding is supported by significantly lower mean ranks in the birth ball group for both posttes pain (17.96 vs. 31.04; p = 0.001) and labor duration (18.50 vs. 30.50; p = 0.003). Notably, the mean duration of labor in the birth ball group was 1.10 hours shorter than in the acupressure group.